Factors influencing consumers’ perception towards counterfeit luxury brands in clothing - Muhamad Hafiz Mohd Radzi; Nur Mahfuzah Musa; Nur Nasirah Abu Yamin; Slow Jee Chui (2016)
The purpose of this study is to understand the factors that affect consumers’ perception towards buying counterfeit of luxury brand in clothing. Particularly we are interested in the factors; social status, value consciousness, post purchase and product involvement. Total of 384 completed the questionnaire that contained three parts. Part A contained 7 questions for data collection regarding demographics of the participants. Part B contained 5 different statement related consumer perception. And lastly part C contained 20 statements related to the factors in this study which were social status, value consciousness, post purchase and product involvement. Collected data were tested using SPSS software program. For the finding, all the factors have positive significant relation with consumers’ perception.